The influence of Au-NP thickness coated on side-polished fiber on the properties of mode-locked erbium-doped fiber laser - Mahmud, N.N.H.E.N.; Awang, N.A.; Zalkepali, N.U.H.H.; Latif, A.A.; Muhammad, N.A.M.; Zamri, A.Z.M. (Elsevier, 2023)
This study introduces gold nanoparticles (Au-NPs) coated on side-polished fiber (SPF) as a saturable absorber (SA) material in the development of a mode-locked erbium-doped fiber laser (EDFL). The measurements were taken at various Au-NP thicknesses of 10, 20, 30, and 40 nm. The SPF was coated with Au-NPs using a Quorum sputter coater by varying the sputtering time of 100, 200, 300, and 400 s at the corresponding thicknesses of 10, 20, 30, and 40 nm. The mode-locked EDFL produced a consistent pulse train with pulse intervals of 25.77 ns, 16.45 ns, 17.92 ns, and 21.55 ns, corresponding to repetition rates of 38.90 MHz, 60.79 MHz, 55.80 MHz, and 46.49 MHz for Au-NP thicknesses of 10, 20, 30, and 40 nm, respectively. Thus, by its ability to tune the repetition rate and pulse duration at different Au-NP thicknesses, the Au-NP SPF SA shows great promise for future optical communications and optoelectronics applications.